Students Motivation and Mathematical Problem Solving Enhancement through SFAE (Student Facilitator and Explaining) in Problem-Solving Strategies - Trisnawati Trisnawati; Wanda Nugroho Yanuarto (Indonesian Journal of Mathematics Education, 2020)
This study was employed to enhance learning motivation and mathematical problem-solving abilities of class VIII A students of SMP Negeri 7 Purwokerto through SFAE learning with problem-solving strategies. The subjects of this study were 31 students of class VIII A SMP Negeri 7 Purwokerto. This study is a Classroom Action Research (CAR), which was conducted collaboratively and participative. The action research was carried out in 3 cycles, with each cycle consisting of 2 meetings. Students were given a questionnaire to measure learning motivation and a test to measure their mathematical problem-solving abilities at the end of each cycle. Data collection techniques in this study include observation, questionnaires, tests, and documentation. Data analysis was carried out by descriptive qualitative and quantitative. The finding showed that implementing of SFAE learning with problem-solving strategies could increase students’ learning motivation and mathematical problem-solving abilities. The study found that (1) The average percentage of the overall learning motivation questionnaire is steadily increased from 61.71% in cycle one to 68.10% in cycle two and 76.03% in cycle three. (2) The average percentage of student tests for problem-solving abilities in cycle one also significantly increases from 35.21% to 53.20% in cycle two and 79.61% in cycle three. The average student test rate for each indicator of problem-solving ability has met the study’s success criteria.